Umberto Eco in His Own Words - Sørensen, Bent; Thellefsen, Torkild (Semiotics, Communication and Cognition SCC, 2017)
Hitherto, there has been no book that attempted to sum up the breadth of Umberto Eco's work and it importance for the study of semiotics, communication and cognition. There have been anthologies and overviews of Eco's work within Eco Studies; sometimes, works in semiotics have used aspects of Eco's work. Yet, thus far, there has been no overview of the work of Eco in the breadth of semiotics. This volume is a contribution to both semiotics and Eco studies. The 40 scholars who participate in the volume come from a variety of disciplines but have all chosen to work with a favorite "ation from Eco that they find particularly illustrative of the issues that his work raises. Some of the scholars have worked exegetically placing the "ation within a tradition, others have determined the (epistemic) value of the "ation and offered a critique, while still others have seen the "ation as a starting point for conceptual developments within a field of application. However, each article within this volume points toward the relevance of Eco -- for contemporary studies concerning semiotics, communication and cognition